The Hadith of Wadi'ah and Wakalah: Historical Critique and Contextual Analysis in Modern Islamic Economic Law - Minhatul Maula; Wandi Wandi; Moh. Najib; Dadah Dadah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The concepts of Wadi’ah and Wakalah are generally referred to in hadith as the foundation for building economic transactions. However, when these concepts are applied in the modern context, many challenges arise, such as changes in social structure, technological advancements, globalization, and the complexity of economic transactions. This study aims to analyze the hadiths that form the basis of the concepts of Wadi’ah and Wakalah historically and to examine how these two concepts can be effectively applied in contemporary economics. Through a literature review method and a descriptive approach, this study uses data sources to analyze hadith related to Wadi’ah and Wakalah and their application in the context of contemporary Islamic economics. The research findings indicate that through historical criticism, it is understood that the application of these hadiths must be adapted to the continuously evolving social and economic context. Ai contextual approach allows for the flexibility in applying the concepts of Wadi’ah and Wakalah to address contemporary economic challenges, including those in the bankng sector, Islamic fintech, investments, and other service industries. The implications of these two concepts emphasize the importance of trust, responsibility, and transparency in creating ethical business practices that align with Sharia principles. By combining Islamic values with modern economic innovations, these concepts offer ethical and just solutions to meet the increasingly complex needs of modern society.